Academic Burnout of Elementary School Students in Lamongan - Moh. Vito Miftahul Munif; M. Naqouib Ashrofun Nashr (Tarsib: Jurnal Program Studi PGMI, 2025)
Academic burnout is an increasingly prevalent issue among students, including those at the elementary school level, due to rising academic demands and learning pressures. This condition has the potential to hinder students’ learning well-being and academic development. This study aimed to analyze the level of academic burnout among elementary school students in Lamongan Regency. The research employed a quantitative approach with a descriptive design. The research subjects consisted of 41 elementary school students selected as the study sample. Data were collected using an academic burnout questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics with the assistance of SPSS, including minimum and maximum scores, mean, standard deviation, and categorization of academic burnout levels. The results showed that students’ academic burnout scores ranged from 24 to 96, with a mean score of 69.39 and a standard deviation of 15.377. Based on the categorization results, the majority of students were classified as having a high level of academic burnout (53.66%), followed by a moderate level (41.46%) and a low level (4.88%). These findings indicate that academic burnout is a dominant condition experienced by elementary school students in Lamongan Regency, highlighting the need for attention and intervention from schools and educators to reduce students’ academic burnout levels.